Environmental Characteristics of Modern Systems of Domestic Use of Fuel. Part 1 - B. S. Soroka; V. V. Horupa (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
The analysis of the environmental component of the processes of natural gas burning in atmospheric burners of domestic gas stoves has been carried out. The computational and experimental studies of the harmful substances formation by combustion of natural gas have been performed. The chemical equilibrium of the NO–O2–NO2 system was considered. The thermodynamic analysis of transformation of the system during a process of natural gas (methane-air mixture) combustion has been tested. Despite an essential (sometimes – by the order(s)) difference between the thermodynamically equilibrium concentration of the nitrogen oxides [NOx]eq and the local, actually measured values [NOx] = [NO] + [NO2], the [NO]eq values could be served as the qualitative indicators of actual values of [NOx] concentrations. In the combustion processes natural gas and other fuels combustion at high temperatures [NO] >> [NO2] for both equilibrium and measured concentrations. By moderate and low local temperatures up to 600 K the equilibrium concentration [NO2]eq → [NO]eq in order of magnitude. Under some compositions of burning mixture the correlation could be set as [NO2] >> [NO], resulting in great danger for the human health. With regard to the formation of particularly toxic NO2 effluents observed in some cases, an influence of the reaction temperature and the composition of the combustible mixture on the possibility of nitrogen dioxide formation in the combustion products have been analyzed. A methodology for the experimental study of the harmful emissions formation has been proposed while the computerized firing rig has been developed for studying the combustion of hydrocarbon gases in burners of household stoves. An influence of the coefficient of primary air excess on the СО, NO, NO2 formation has been revealed and the possibility of appearance the emissions of a high concentration of nitrogen dioxide has been demonstrated.